PERBEDAAN PANJANG SIKLUS DAN LAMA ESTRUS SERTA HUBUNGANNYA DENGAN UMUR PADA SAPI PERANAKAN ONGOLE (PO) DAN SAPI SIMMENTAL-PO (SIMPO) DI YOGYAKARTA - , NANTI UJARWATI; , drh. Erif Maha Nugraha Setyawan, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The needs of beef cattle for meat consumption in Indonesia is increasing, it is necessary to attemp to improve the reproductivity of beef cattle. The example of beef cattle in Indonesia are cows PO and SimPO where maintenance with age variation. SimPO is hybrid cows. It is found a problem on cow reproductive performance hybrid. The purpose of this study is to determine difference of the length of estrous cycle, duration of estrus and the relationship with age in cows PO and SimPO. This research began on April 20, 2013 to May 25, 2013 in some pleaces of Yogyakarta special regency such as Piyungan, Seyegan, Nanggulan, and Lendah. A total of 17 samples of PO and 10 samples of PO used in this study. This study was conducted using a survey and interviews to farmers about age of cows, length of estrous cycle and direct observation of the duration of estrus. The data obtained were analyzed statistically using Mann Whitney test to determine difference the length of estrous cycle and duration of estrus in cow PO and SimPO. To determine relationship with age on cows PO and SimPO was used Spearmanâs rho test. The result showed that cows PO has ranged length of estrous cycle 22.06Â±5.96 day and duration of estrus 28.29Â±12.45 hours. Cows SimPO showed the length of estrous cycle 20.2Â±1.87 day and duration of estrus 67,8Â±13.61 hours. The results obtained in this study showed that there was no significant difference (P>0,05) between cows PO and SimPO about length of estrous cycle, but there was significant difference (P<0,05) of the duration of estrus. SimPO had longer duration of estrus. There was no relationship significant (P>0,05) between age with the length of estrous cycle and duration of estrus in cows PO although SimPO.